(3WHbGJ GdCees - (3CHh GdbGSe UGYO Hf CMeO Hf YHO GdQMef GdbQWHj GdCfOdSj, UGYO GdCfOdSj,J (B462 (3g` s ((3EHQGgje Hf GdeHdW GdTGaYj s)
(3ChdgG (B:s
(3GYde Cf LejY GdfGSef eTGQb GdCQV heZGQHgG hEf cGfhG fhYkG hGMOkG aEfge eJejRhf HKdGKI CTjGA s
(3BNQgG (B:s
(3gPG eG MVQfj MaXg ef JSejI YdeGA GdCee hGdMeO ddg hMOg hUdi Gddg Ydi SjOfG eMeO hBdg hUMHg hSde s
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B186s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B268 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs